Detection of early impairment of coronary flow reserve in patients with systemic sclerosis. Issue 9 (15th August 2003) - Montisci, R; Vacca, A; Garau, P; Colonna, P; Ruscazio, M; Passiu, G; Iliceto, S; Mathieu, A
Abstract : Objective: To investigate whether coronary flow reserve (CFR), measured by a new non-invasive method, is impaired early in patients with systemic sclerosis (SSc) and whether CFR impairment correlates with clinical or functional measures, or both. Methods: 27 patients with SSc without clinical evidence of ischaemic heart disease and 23 control group subjects matched for age and sex were studied. CFR was evaluated in the left anterior descending coronary artery (LAD) with a new non-invasive method: contrast (Levovist) enhanced transthoracic Doppler during adenosine infusion. The pulsed wave Doppler examination of blood flow velocity was recorded in the LAD at rest and after maximum vasodilatation by adenosine infusion. Results: In patients with SSc, without clinical evidence of ischaemic heart disease, CFR was impaired (p=0.0001). 14/27 patients with SSc had severe reduction of the CFR (⩽2.5) compared with controls (p=0.002). A non-significant trend between mean CFR and the severity and duration of the disease was also seen. Conclusions: CFR is often reduced in patients with SSc, suggesting early preclinical cardiac involvement in SSc. This impairment in coronary microvasculature is detectable by a non-invasive echocardiographic method and in this study was more common in the diffuse form of SSc.